Ejecutor coactivo:excesos en la aplicacion de medidas cautelares previas al procedimiento de cobranza coactiva - Rojas Alas, Cristhian Paúl (2018)
In the present investigation is oriented to establish, on the basis of jurisprudential and dogmatic criteria, the affectation of the principle of legality and legal security in tax matters before the application of the unsuccessful collection criterion for the granting of Precautionary Measures Prior to the Coercive Collection Procedure , established in Article 56 of the Tax Code, and the urgent need to regulate exhaustively causal or assumptions that configure the aforesaid presumption; for this, a dogmatic development of legal institutions immersed in the research problem in a systematic and comprehensive manner has been carried out. In addition, it is based on the premise that the current regulations must always be consistent with the general principles of law in communion with the constitutional text, therefore, the correct interpretation and application thereof, can not violate fundamental rights or general principles of the right. Now, we postulate that the power of the tax administration, established and embodied in the creation of procedural rules aimed at regulating administrative actions within tax procedures, must be exercised on criteria of reasonableness, creating adjective standards that constitute true procedural guarantees, and in the case of prior precautionary measures, on an exceptional basis. However, by not having a correctly regulated norm, one can appreciate the denaturalization of the previous precautionary measures, since the tax authority is envestida by excessive prerogatives, which do not notice limitation or any parameter. Finally, considering a clear constitutional effect that is verified through the results obtained by the present investigation, product of the analysis of the Resolutions of the Fiscal Court issued in relation to the norm in controversy is that it can be concluded that the formulation of modifications is necessary legislative, that can incorporate delimitations of the causes or suppositions that configure the Presumption of unfruitful collection,whose analysis of the behavior of the tributary debtor would only be able to lock Precautionary Measures Prior to the Procedure of Coercive Collection.